Izpitna vprašanja iz ginekologije in perinatologije (University of Maribor Press, 2021)
Gynecology and Perinatology Exam Questions. The study material entitled ’Gynecology and Perinatology Exam Questions’ is the first material of its kind published in Slovenia to systematically cover sample questions and answers used for Obstetrics and Gynecology tests at graduate medical schools. This is a work created by twenty-three authors, obstetrics & gynecology residents, and edited by four editors. Eighty-eight chapters contain 3520 gynecology, obstetrics, and neonatology questions. Among the answers provided, only the single best answer (SBA) is correct. Single Best Answer format is a written examination form of multiple-choice questions with only one being the best answer. The questions and answers in this publication can also be used to test students in other disciplines, such as nursing, physiotherapy etc. However, obstetrics & gynecology residents can also use it when studying for the board examination.